A combination of mupirocin and acidic fibroblast growth factor for nipple fissure and nipple pain in breastfeeding women: protocol for a randomised, double-blind, controlled trial. Issue 3 (27th March 2019) - Lv, Xiaofang; Feng, Rui; Zhai, Jingbo
Abstract : Introduction: Nipple fissure and nipple pain are common complaints among breastfeeding mothers. Studies found that mupirocin was effective in preventing and treating infections of damaged nipple and nipple pain. Acidic fibroblast growth factor (aFGF) plays an important role in wound healing. However, current evidence on the efficacy and safety of mupirocin plus aFGF for nipple fissure and nipple pain in breastfeeding women is inconclusive due to the lack of well-designed randomised controlled trials on this topic. The purpose of this study is to test the hypothesis that mupirocin plus aFGF is more effective than mupirocin alone for nipple fissure and nipple pain in breastfeeding women. Methods and analysis: This study is a randomised, double-blind, single-centre, parallel-group clinical trial. A total of 120 breastfeeding women with nipple fissure and nipple pain will be randomly assigned to either mupirocin plus aFGF group or mupirocin plus placebo group according to a computer-generated random allocation sequence. The treatment period lasts 14 days. The primary outcome is nipple pain intensity measured by the Visual Analogue Scale on day 14 during the treatment period. Secondary outcome measures include time to complete nipple pain relief, changes in the Nipple Trauma Score, time to complete healing of nipple trauma, quality of life measured by the Maternal Postpartum Quality of Life (MAPP-QOL) Questionnaire, the frequency of breast feeding, the rate of breastfeeding discontinuation, weight change in infants and adverse events. Ethics and dissemination: The study has gained approval from the Ethics Review Committee of Tianjin Central Hospital of Gynaecology Obstetrics on 22 January 2018 (approval no. 2018KY001). We plan to publish our research findings in a peer-reviewed academic journal and disseminate these findings in international conferences. This study has been registered with the Chinese Clinical Trial Registry. Trial registration number: ChiCTR1800017248.